Diagnóstico del liderazgo educativo y su influencia en la conducta de los estudiantes del Colegio Nacional Técnico Agropecuario Abdón Calderón Muñoz, de la parroquia Palmales, cantón Arenillas, periodo lectivo 2012-2013. - Herrera Torres, Alcívar Fernando (2013)
Transformational leadership as a means to develop an educational management in decentralized context is a central theme in ongoing discussion to guide the search for answers, both theoretical and pragmatic solutions to the problems underlying around management centers Education School. Within this framework of epistemic reference herein lies in generating an approximation to the fundamental education management in a holistic approach, which integrates the dimensions of transfomacional leadership in educational context.